Islamic Republic of Iran - a surprisingly progressive centre of medical tourism - Sobotková, Veronika (Casopis lekaru ceskych, 2022)
The Islamic Republic of Iran is a very progressive state in the field of medical research and its application. Although the country is fully subject to Islamic law (shari'a) and the influence of Shi'ite clerics, the development of medical science is not limited at all; Shi'ite medical ethics (unlike Sunnite) allows most of the modern medical techniques. Due to this attitude, Iran specializes today in many techniques that are prohibited in other countries for religious or ethical reasons. For example, Iranian research on cloning, cell and gene therapy reaches the world level, patients can use a third-party donor program and surrogacy for infertility treatment, the sale of kidney for transplantation was legalized, gender reassignment surgery is performed, and the country is a centre of cosmetic surgery. All of these services (excluding transplantation) are also offered to foreign patients. Thanks to these unlimited possibilities, high quality and low price, Iran has been currently gaining a strong position in the medical tourism market, not only in the Middle East region, but also worldwide.
Keywords: Islamic bioethics; islám; Írán; Medical Tourism; medical tourism; Ethics, Medical; Humans; Iran; Tissue Donors; Shi'ite Islam; Islam; dárci tkání; lékařská etika; lidé; zdravotní turistika